Effects of astaxanthin on microRNA expression in a rat cardiomyocyte anoxia-reoxygenation model - Zhang, Xinxin; Xu, Min; Cai, Shuilin; Chen, Bei; Lin, Hetong; Liu, Zhiyu (Frontiers in Pharmacology, 2023)
The protective effects of astaxanthin against myocardial ischemia-reperfusion injuries are well documented, although the mechanisms are not defined. We measured the effects of astaxanthin pretreatment on microRNA expression in a rat myocardial cell anoxia-reoxygenation injury model. After anoxia-reoxygenation injury, in a dose dependent manner, astaxanthin increased cell viability, superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activity, decreased lactate dehydrogenase (LDH) and malondialdehyde (MDA) levels, downregulated protein expression of caspase-3, caspase-8, nuclear factor erythroid-2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1), and upregulated the Bcl-2/Bax ratio. High-throughput sequencing and qPCR showed that microRNAs rno-miR-125b-5p and rno-let-7c-1-3p were differentially expressed (|log2|≥0.585, q<0.1) between the normal, anoxia-reoxygenation, and astaxanthin (1.25 μM) groups. KEGG (Kyoto Encyclopedia of Genes and Genomes) and GO (Gene ontology) pathway enrichment analyses showed that TNF signaling, axon guidance, NF-κB signaling pathway, and other pathways displayed differentially expressed microRNA target genes associated with myocardial injuries. These results suggested that the target genes of rno-miR-125b-5p were enriched in inflammation and apoptosis-related signaling pathways. Also, the results imply that simultaneous targeting of these related signaling pathways could significantly prevent myocardial anoxia-reoxygenation injury in the presence of astaxanthin.